Validity and reliability of Child Perception Questionnaire (CPQ(11-14)) by Rasch Analysis in Turkish children - KARGÜL, BETÜL; BEKİROĞLU, GÜLNAZ NURAL (ELSEVIER SCIENCE BV, 2017)
Assessment for the reproducibility of the answers to the Child Perception Questionnaire (CPQ(11-14)) in different languages with test-retest exercises have importance to be acceptable in other populations. The present study is to evaluate the validity and reliability of Child Perception Questionnaire for ages 11-14 (CPQ(11-14)) with 37 items by means of Rasch Analysis in a group of Turkish population. 133 children aged 11-14 years old were included to the study. CPQ11-14 was administered at their first visit, as well as Facial Image Scale questions. After two weeks, CPQ11-14 was re-applied to a subgroup (n = 25) of the children. The construct validity of the CPQ11-14 data was assessed by using Rasch Analysis. Intra-class Correlation Coefficient was calculated with the CPQ11-14 scores of first and second visits. Cronbach's alpha coefficient was obtained for evaluating internal consistency. According to Rasch Analysis, mean item infit +/- sd was 0.98 +/- 0.25; mean item outfit +/- sd was 1.08 +/- 0.91. Item and person separation indices and reliabilities were calculated as 3.34 and 2.42; 0.92 and 0.85, respectively. The Pearson's correlation coefficient between the total scores of CPQ(11-14) and the Facial Image Scale was found as 0.74 (p < 0.001). Cronbach's alpha coefficient was 0.93 and ICC was 0.90 for the total scale. The findings of the present study showed that the Turkish version of CPQ(11-14) with 37 items is valid and has excellent reliability. (C) 2016 Japanese Society of Pediatric Dentistry. Published by Elsevier Ltd. All rights reserved.
Keywords: Child Perception Questionnaire (CPQ); Oral Health Related Quality of Life (OHRQoL); Validity; Reliability; Caries; QUALITY-OF-LIFE; ORAL-HEALTH; VERSION